1998
DOI: 10.1046/j.1365-2982.1998.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

SB‐207266: 5‐HT4 receptor antagonism in human isolated gut and prevention of 5‐HT‐evoked sensitization of peristalsis and increased defaecation in animal models

Abstract: SB-207266 is a new 5-HT4 receptor antagonist which in a pilot study reduced the symptoms of irritable bowel syndrome. To help validate this and further studies, we examined the ability of SB-207266 to antagonize at the human 5-HT4 receptor (human isolated intestine) and to affect the mechanisms of peristalsis (guinea-pig isolated ileum) and defaecation (conscious, fed mice). In the human intestine, the potency of 5-HT4 receptor antagonism (pKB 9.98) was similar to that previously demonstrated using a guinea-pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…35,49,50 Overall, animal and human studies have shown that 5-HT 4 receptor antagonists have a minimal effect on normal healthy volunteers, but do ameliorate the effects of administered 5-HT or 5-HT 4 receptor agonists. 49,51 These data suggest that piboserod works in disorders of excess 5-HT but not in the healthy population. There is concern that piboserod may cause atrial fibrillation because of its effects on atrial 5-HT 4 receptors.…”
Section: -Ht 4 Receptor Antagonistsmentioning
confidence: 90%
“…35,49,50 Overall, animal and human studies have shown that 5-HT 4 receptor antagonists have a minimal effect on normal healthy volunteers, but do ameliorate the effects of administered 5-HT or 5-HT 4 receptor agonists. 49,51 These data suggest that piboserod works in disorders of excess 5-HT but not in the healthy population. There is concern that piboserod may cause atrial fibrillation because of its effects on atrial 5-HT 4 receptors.…”
Section: -Ht 4 Receptor Antagonistsmentioning
confidence: 90%
“…Not only 5-HT 3 receptors but also 5-HT 4 receptors mediate colonic motility and fecal pellet output in response to endogenous or exogenous 5-HT in rodents (2,18,22,24,39,42,43). In mouse, rat, and human intestine, the peristaltic reflex is initiated by mucosal release of 5-HT and activation of 5-HT 4 receptors on CGRP sensory neurons, which is relayed to VIP/nitric oxide inhibitory motor neurons and to ACh/tachykinin excitatory motor neurons (17) Further studies are needed to address whether 5-HT 4 receptors are involved in mediating the stimulation of colonic motility in response to restraint stress in rats.…”
Section: Discussionmentioning
confidence: 99%
“…To address whether PYY 3-36 -induced suppression of the colonic response to a novel environmental stress involves activation of corticotrophin-releasing factor receptor 2 (CRF 2 ) inhibitory pathways (42), we used the CRF 2 antagonist, astressin 2 -B (51). Next, we investigated whether PYY and PYY inhibitory action can modulate the prokinetic effect of cholinergic and serotonergic transmitters (22,64) using exogenous serotonin (5-HT) precursor, 5-hydroxytryptophan (5-HTP) that mimics a state of endogenous 5-HT production and release (52) and the long-acting muscarinic agonist, bethanechol. The role of Y 2 in mediating PYY inhibitory action was further assessed pharmacologically with the selective Y 2 antagonist, BIIE0246 (3,12), and potential site of action by assessing the expression of Y 2 receptor at the gene and protein levels in the mice colon.…”
mentioning
confidence: 99%